2019
DOI: 10.1039/c9cp04073k
|View full text |Cite
|
Sign up to set email alerts
|

A combined experimental and computational study on the reaction dynamics of the 1-propynyl radical (CH3CC; X2A1) with ethylene (H2CCH2; X1A1g) and the formation of 1-penten-3-yne (CH2CHCCCH3; X1A′)

Abstract: Center-of-mass velocity flux contour maps for the reactions of 1-propynyl with ethylene for the atomic hydrogen loss leading to 1-penten-3-yne.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 113 publications
0
11
0
Order By: Relevance
“…42 Crossed molecular beams studies of the 1-propynyl radical (H 3 CCC) with ethylene (C 2 H 4 ) revealed the barrierless gas-phase synthesis of distinct C 5 H 6 isomers. 43 The 1-propynyl radical (H 3 CCC) was found to add barrierless to the double bond of ethylene (C 2 H 4 ) leading to a long-lived C 5 H 7 complex(es) ultimately forming 1penten-3-yne (K) along with the atomic hydrogen solely from the ethylene reactant. 43 Furthermore, the methylidyne radical (CH) plus 1,3-butadiene (CH 2 CHCHCH 2 ) reaction was initiated by addition of the CH radical to one of the terminal carbon atom and/or carbon−carbon double bond of 1,3butadiene without entrance barrier; this reaction resulted in the preparation of three-membered ring products cis-and trans-3-vinyl-cyclopropene (A, B).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…42 Crossed molecular beams studies of the 1-propynyl radical (H 3 CCC) with ethylene (C 2 H 4 ) revealed the barrierless gas-phase synthesis of distinct C 5 H 6 isomers. 43 The 1-propynyl radical (H 3 CCC) was found to add barrierless to the double bond of ethylene (C 2 H 4 ) leading to a long-lived C 5 H 7 complex(es) ultimately forming 1penten-3-yne (K) along with the atomic hydrogen solely from the ethylene reactant. 43 Furthermore, the methylidyne radical (CH) plus 1,3-butadiene (CH 2 CHCHCH 2 ) reaction was initiated by addition of the CH radical to one of the terminal carbon atom and/or carbon−carbon double bond of 1,3butadiene without entrance barrier; this reaction resulted in the preparation of three-membered ring products cis-and trans-3-vinyl-cyclopropene (A, B).…”
Section: Introductionmentioning
confidence: 99%
“…The most stable C 5 H 6 isomer cyclopentadiene (L) was confirmed to be the dominating C 5 H 6 isomer; the four-membered cyclic isomer 3-methylenecyclobut-1-ene (J) could not be detected . Besides hydrocarbon flames, C 5 H 6 isomers can also be formed in bimolecular reactions. Li et al computed the C 5 H 7 PES exploiting the hybrid density functional B3LYP/CBSB7 level of theory via the reaction of the ethynyl (C 2 H) radical with propene (C 3 H 6 ) . Formation of the atomic hydrogen emission product, 2-methyl-1-buten-3-yne (H), was initiated through an ethynyl (C 2 H) addition to the carbon–carbon double bond of propene (C 3 H 6 ) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Experimental studies along with theoretical calculations provide compelling evidence that critical C 5 H x isomers (x = 3 -7) can be formed via bimolecular reactions involving neutralneutral reactions. [8][9][10][11][12][13][14][15][16][17][18][19][20][21] Crossed molecular beams reactions of the ground state carbon atoms (C ( 3 P)) with vinylacetylene (HCCCHCH 2 ) revealed the formation of distinct C 5 H 3 isomers. 15 The carbon atom was found to attack the double and/or triple bond of vinylacetylene without entrance barrier forming long-lived C 5 H 4 complex(es) eventually decomposing via atomic hydrogen loss to the 2,4-pentadiynyl-1 radical (i-C 5 H 3 ; H 2 CCCCCH) and the 1,4-pentadiynyl-3 radical (n-C 5 H 3 ; HCCCHCCH).…”
Section: Introductionmentioning
confidence: 99%
“…The final product was 1-penten-3-yne (C 5 H 6 ; CH 2 CHCCCH 3 ) with the hydrogen atom ejected solely from ethylene reactant (Scheme 1). 21 The aforementioned pathways exposed that the underlying formation mechanisms of C 5 hydrocarbon species are very complex and still poorly understood. To further shed light on the chemistry and chemical dynamics of C 5 hydrocarbon species, we present here the results of a study of the bimolecular reaction of the methylidene radical (CH; X 2 Π) with 1,3-butadiene (C 4 H 6 ; X 1 A g ) along with their partially deuterated reactants at collision energies of 20.8 kJ mol -1 under single-collision conditions.…”
Section: Introductionmentioning
confidence: 99%